An exploratory study on symptoms of problem behaviors among juvenile offenders - Abdul Rahman Ahmad Badayai; Rozainee Khairudin; Khaidzir Haji Ismail; Wan Shahrazad Wan Sulaiman (Penerbit Universiti Kebangsaan Malaysia, 2016)
This study examined different types of symptoms of problem behaviours among juvenile offenders. Various symptoms of problem behaviours such as social problem, thinking problem, attention problem, rule-breaking behaviour, and aggressive behaviour can be predicted among young juvenile delinquents. There were 404 juvenile offenders participated in the study, consisted of 280 males and 124 females. All respondents convicted with seven different offenses. Prior to that, three research questions were developed: 1. Are there differences in the symptoms of problem behaviours among different types of juvenile offenders? 2. Are there gender differences in the symptoms of problem behaviours among young offenders? 3. Are there any age differences in the symptoms of problem behaviours among juvenile offenders? The results showed there were different symptoms of problem behaviours among young offenders. Gender differences profile also showed mean differences in each symptom of problem behaviours among juvenile offenders. One-way ANOVA results showed significant differences in thought problem F (7) = 2.748, p< .01 and attention problem F (7) = 25.948, p < .01 among different types of delinquent behaviours. Moreover, t-test results revealed that gender differences were significant in social problem; t (402) = -2.710, p<.01, thought problems; t (402) = -2.476, p<.05, attention problem; t (402) = -4.841, p<.001, and aggressive behaviour; t (402) = -3.165, p<.001, p< .01.